2010
DOI: 10.1021/nn100714v
|View full text |Cite
|
Sign up to set email alerts
|

Topological Transitions in Carbon Nanotube Networks via Nanoscale Confinement

Abstract: Efforts aimed at large-scale integration of nanoelectronic devices that exploit the superior electronic and mechanical properties of single-walled carbon nanotubes (SWCNTs) remain limited by the difficulties associated with manipulation and packaging of individual SWNTs. Alternative approaches based on ultrathin carbon nanotube networks (CNNs) have enjoyed success of late with the realization of several scalable device applications. However, precise control over the network electronic transport is challenging … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
0
24
0
Order By: Relevance
“…As shown in the Fig. 4a, nanotubes in both edges are more highly aligned because of the capillary force-induced assembly of SWCNTs 30,32 . Highly excited electrons for V a ¼ 0.8V b constantly transfer their energy to the nanotube lattice.…”
Section: I-v Characterization and Alternating Voltage Pulsesmentioning
confidence: 93%
See 2 more Smart Citations
“…As shown in the Fig. 4a, nanotubes in both edges are more highly aligned because of the capillary force-induced assembly of SWCNTs 30,32 . Highly excited electrons for V a ¼ 0.8V b constantly transfer their energy to the nanotube lattice.…”
Section: I-v Characterization and Alternating Voltage Pulsesmentioning
confidence: 93%
“…The basic steps for building organized SWCNT lateral architectures fabricated using the template-guided fluidic assembly process [30][31][32] , are as follows. First, a 300-nm-thick polymethyl methacrylate photoresist is deposited on a substrate and baked at 160°C for 90 s. Second, polymethyl methacrylate patterns are constructed on the substrate using electronbeam lithography to build nanoscale channels, which form templates for building the test architectures and these templates are then developed in the solution (methyl isobutyl ketone/isopropyl alcohol ¼ 1:3) for 100 s followed by a 30-s rinse in isopropyl alcohol solution.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, using self-assembly and fl uidic assembly, researchers have reported that the alignment of SWNTs strongly depends on the relation between the length of SWNTs and the width of the pattern (trench). [ 47,48 ] Park et al assembled SWNTs on the desired position by an ion-exchange process. Taking advantage of the fl uidic interface and electrode/ nanotube geometry, we have been able to assemble aligned SWNTs onto features from the suspension.…”
Section: Communicationmentioning
confidence: 99%
“…With the adhesion or friction between tubes and substrates affecting the fabrication and the performance of SWNT-based nanodevices [6][7][8][9][10][11][12], it is also very important to develop an understanding of how these processes affect the mechanical shear stress between CNTs and gold surfaces.…”
Section: Introductionmentioning
confidence: 99%